Transcriptional expression of m6A and m5C RNA methyltransferase genes in the brain and fat body of honey bee adult workers - Bataglia, Luana; Simões, Zilá Luz Paulino; Nunes, Francis Morais Franco (Frontiers in Cell and Developmental Biology, 2022)
Honey bee (Apis mellifera) adult workers change behaviors and nutrition according to age progression. Young workers, such as nurses, perform in-hive tasks and consume protein-rich pollen, while older workers (foragers) leave the colony to search for food, and consume carbohydrate-rich nectar. These environmentally stimulated events involve transcriptional and DNA epigenetic marks alterations in worker tissues. However, post-transcriptional RNA modifications (epitranscriptomics) are still poorly explored in bees. We investigated the transcriptional profiles of m6A and m5C RNA methyltransferases in the brain and fat body of adult workers of (i) different ages and performing different tasks (nurses of 8 days-old [N-8D] and foragers of 29 days-old [F-29D], sampled from wild-type colonies), and (ii) same-aged young workers caged in an incubator and treated with a pollen-rich [PR] or a pollen-deprived [PD] diet for 8 days. In the brain, METTL3, DNMT2, NOP2, NSUN2, NSUN5, and NSUN7 genes increased expression during adulthood (from N-8D to F-29D), while the opposite pattern was observed in the fat body for METTL3, DNMT2, and NSUN2 genes. Regarding diet treatments, high expression levels were observed in the brains of the PD group (DNMT2, NOP2, and NSUN2 genes) and the fat bodies of the PR group (NOP2, NSUN4, and NSUN5 genes) compared to the brains of the PR group and the fat bodies of the PD group, respectively. Our data indicate that RNA epigenetics may be an important regulatory layer of the development of adult workers, presenting tissue-specific signatures of RNA methyltransferases expression in response to age, behavior, and diet content.